GEOSTATISTICAL STUDY OF LATERAL AND RADIAL DISTRIBUTION OF CONCENTRATIONS OF CHEMICAL ELEMENTS IN THE SOIL OF MODERATE TECHNOGENESIS ZONE (on example of Kyiv suburbia) - Tyutyunnik, Yu.; Shabatura, O.; Daunis-i-Estadella, J. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Average concentrations of chemical elements in the soil depends on the action of natural and techogenic factors and are characterized by different regularities of migration and accumulation in the lateral and radial directions. Study of concentrations of chemical elements in soils of different elementary geochemical landscapes makes it possible to identify some of the important statistically significant regularities of distribution of chemical elements on the territory of Irpin-Bucha-Vorzel of Kyiv suburban area. The analysis of 190 samples from 36 full-profile soil profiles formed the basis of compositional data (CoDa). CoDa is vector product of the measured values ff concentrations of chemical elements in each sample of soil. Geostatistical model biplot of CoDa is a hyperspace of geochemical factors and reasons with dimension corresponding to the amount determined in samples of chemical elements. Projection of hyperspace on the plane with "star" biplot especially together with projection of sampling points can demonstrate the probabilities of indicators of action of various geochemical factors and causes that occur in the study area. Clustering of sampling points occurs in a possible impact of certain factors on the group geochemical samples. The geostatistical parameters obtained by modeling SoDa in La-Ce-Nd 12-dimensional and Fe-Sr-Ga 9-dimensional hyperspaces mark an area of geochemical factor "influence of initial mineral composition of rocks". The area is defined by relevant geostatistical parameters Rb-Sr-Ba in 12-dimensional and Ba-R in 9-dimensional hyperspaces statistically "linked" to the acid-alkaline conditions in soils. Manganese area in the mentioned above area and 6-dimensional hyperspace of Fe mark the oxidationreduction conditions in soils. Area of Pb suggests to determine a pyrogenic component of technogenic influence associated with vehicle emissions. Zn-Cu area is associated with impact of biogenic processes. Relative impact geochemical factors on the elemental composition of the upper (10 cm) layer of soil geochemical factors surveyed area are ranged in row: technogenesis > biogenesis > effect of initial lithogenic basis. The analysis of 6dimensional hyperspace gave general trend to group between areas that are marked Fe-Sr-Ba-Rb (lithological and mineralogical factor) and Pb (technogenesis, especially atmospheric pollution caused by road). For soil sampling points of the subordinate landscapes there is a tendency to highlight grouped areas marked Fe-Sr-Ba-Rb, Zn and Zn, Pb. Geochemical factors and reasons most clearly effect in the analysis SoDa samples taken with reference to the genetic soil horizons than those selected from formal deep layer.